Investigação dos efeitos cardioprotetores do extrato aquoso de Petiveria alliacea l. em ratos espontaneamente hipertensos - Pael, Luana Ale Bertoncello (2024)
Cardiovascular diseases are the primary cause of hospitalizations and deaths globally. Prevention is achievable by addressing behavioral risk factors. The presence of these risk factors can result in high blood pressure. The use of alternative and complementary therapies, such as medicinal plants, is becoming increasingly common as a treatment option due to their active ingredients that can offer prophylactic or therapeutic action in the treatment of diseases or the control of their symptoms. Petiveria alliacea, commonly known as guiné, contains phytochemical compounds that are linked to diuretic properties. The objective of this study was to examine the cardioprotective effects of the ethanol-soluble fraction obtained from the aerial parts of P. alliacea in hypertensive rats treated with isoprenaline. The aerial parts of P. alliacea were collected and infused to obtain the aqueous extract, which was then treated with ethanol to produce the ethanol-soluble fraction of P. alliacea (ESPA). Wistar-Kyoto and spontaneously hypertensive rats were divided into different experimental groups, including naïve, negative control (vehicle 1mL/100g body weight), metoprolol (10 mg/kg), and ESPA (30, 100, and 300 mg/kg). All hypertensive groups received isoprenaline (4.5 mg/kg) subcutaneously once a day for the first 4 days of treatment. Treatment lasted 28 days and was evaluated in terms of renal function, electrocardiographic profile, blood pressure, mesenteric vascular bed reactivity, biochemical markers and histopathology. Treatment with ESPA induced a significant acute natriuretic response. After 28 days of treatment with ESPA at doses of 100 and 300 mg/kg, the animals showed reduced blood pressure and lipid peroxidation levels. This resulted in a reversal of the electrocardiographic alterations and endothelial dysfunction induced by hypertension in the rats. The treatment with ESPA for 28 days induced significant cardioprotective effects in hypertensive rats treated with isoprenaline.These effects appear to be dependent on an antioxidant response associated with the inhibitory effect on angiotensin-converting enzyme.